Diversity of used plant species for producing charcoal and its trade-off in Far-North Region, Cameroon - Todou, G.; Hassan, M.; Ze, Akamba; Kombo, D.; Machewere, S.; Vroumsia, T. (International Journal of Environment, 2017)
The Northern Regions of Cameroon belong to sudano-zambesian region. In these regions, woody species are scarce compared to Guinean-Congolese Region and they undergo the human pressure like abusive exploitation of plants. In order to contribute to valorization of phytogenetic resources and contribute to struggle desert progression in sahelian region, a study on plants diversity which are used to produce charcoal and its trade-off was carried out in Far-North Region of Cameroon. Census of plants species was made on the basis of semi-structured surveys through the producers of charcoal and identification of tree trunks on the sites of charcoal production. Data of trade of charcoal was collected by direct observation and a semi-structured survey questionnaire in Maroua. In total, 25 species grouped in 17 genera and 8 families have been recorded. Acacia and Combretum were the richest genera with four species each. They were quoted as multipurpose species which can be used elsewhere as fruits, timbers, medicinal plants or essential oils and exudates. In Maroua almost, 98 % of households use charcoal for heating. In the absence of the charcoal, up to 60 % of those use firewood, 18.46 % use domestic gas and 18.46% use kerosene. Because of poverty and unemployment, people of primary education are mostly charcoal sellers.  INTERNATIONAL JOURNAL OF ENVIRONMENTVolume-6, Issue-2, Mar-May 2017, Page: 19-29